Effect of Dietary Grape Pomace and Seed on Ewe Milk and Meat Quality of Their Suckling Lambs - V. C. Resconi; M. Pascual-Alonso; L. Aguayo-Ulloa; G. C. Miranda-de la Lama; S. Alierta; M. M. Campo; J. L. Olleta; M. Villarroel; G. A. María (Journal of Food Quality)
The effect of wine by-products in the feeding of ewes on fatty acid composition of milk and meat of their suckling lambs and the sensory quality of the meat was investigated. Forty-two ewes were fed during the second half of gestation and lactation one out of three treatments: a control diet based on a commercial concentrate and two concentrates supplemented with either 10% grape pomace or 5% grape seed. In addition, all animals had ad libitum access of Lucerne chaff. The control group showed lower concentration of saturated fatty acids (mainly in short and medium chain) and higher monounsaturated fatty acids (mainly oleic acid) in the milk fat, being the total polyunsaturated fatty acids unchanged. However, this variation was not reflected in the meat of the suckling lambs, where only few differences in individual fatty acids were found, such as linoleic acid being highest in the pomace treatment. Spicy and metallic flavours were increased in the wine by-products groups, but overall liking was not affected. The by-products added to the diets may be a good way to reduce costs on feeding and waste, but they were not able to provide a healthier fatty acid profile, neither in milk nor in the meat of the suckling lambs.